2017
DOI: 10.1590/1982-3703001432016
|View full text |Cite
|
Sign up to set email alerts
|

Concepções de Adolescência e Educação na Atuação de Profissionais do CAPSi

Abstract: Resumo O objetivo do estudo aqui apresentado foi apreender as concepções sobre adolescência e educação dos profissionais do Centro de Atenção Psicossocial Infanto-Juvenil (CAPSi) que embasam sua atuação, em especial aquela que se desenvolve junto ao processo de escolarização dos adolescentes que frequentam esse serviço. Foram entrevistados 11 profissionais que atuam em um CAPSi: uma assistente social, um psiquiatra, duas psicólogas, duas enfermeiras, quatro terapeutas ocupacionais e a coordenadora. Para a tess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
0
2
0
3
Order By: Relevance
“…Such data corroborate research that apprehended the conceptions about adolescence carried out with professionals from a Centro de Atenção Psicossocial Infantojuvenil -CAPSi (Child and Adolescent Psychosocial Care Center in free translation) in Santa Catarina. 22 These professionals demonstrated difficulty in breaking a naturalized view of the adolescent, understood as a phase of conflicts, without locating it as a development process and signified by the society in which it is built. 22 Adolescence is a phase with greater intrapersonal and social vulnerability, so individuals have exercised self-injury to relieve negative feelings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data corroborate research that apprehended the conceptions about adolescence carried out with professionals from a Centro de Atenção Psicossocial Infantojuvenil -CAPSi (Child and Adolescent Psychosocial Care Center in free translation) in Santa Catarina. 22 These professionals demonstrated difficulty in breaking a naturalized view of the adolescent, understood as a phase of conflicts, without locating it as a development process and signified by the society in which it is built. 22 Adolescence is a phase with greater intrapersonal and social vulnerability, so individuals have exercised self-injury to relieve negative feelings.…”
Section: Discussionmentioning
confidence: 99%
“…22 These professionals demonstrated difficulty in breaking a naturalized view of the adolescent, understood as a phase of conflicts, without locating it as a development process and signified by the society in which it is built. 22 Adolescence is a phase with greater intrapersonal and social vulnerability, so individuals have exercised self-injury to relieve negative feelings. 12 In a cross-sectional research that identified motivations for self-injury among 856 adolescents, 9 it was found that 103 reported episodes of NSSI, and the most reported reason is to get relief from a bad feeling.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda sobre o tema das portas de entrada, estudos têm demonstrado que parcela significativa de encaminhamentos aos CAPSi está relacionada às dificuldades nos contextos escolares (Beltrame & Boarini, 2013;Delfini et al, 2009;Luckow & Cordeiro, 2017). De acordo com Delfini et al (2009), a escola tem sido crescentemente um espaço onde são evidenciadas e reconhecidas dificuldades de crianças e adolescentes em corresponderem a certo padrão de ideal, que vão desde às capacidades cognitivas e de produtividade escolar, às inadequações comportamentais no espaço escolar-institucional (comportamentos de rebeldia, agressividade, apatia etc.).…”
Section: Portas De Entrada Para O Capsiunclassified
“…Ademais, também estão presentes trabalhos sobre acompanhamento terapêutico (Engel, Ghazzi, & Silva, 2013) e problematizações sobre os processos de medicalização da vida (Decotelli, Bohrer, & Bicalho, 2013). Destacam-se, ainda, artigos que apresentam intersecções entre saberes/disciplinas científicas, tais como Direito e Psicologia (Carvalho & Perucchi, 2016), e discussões sobre infância e família no campo da saúde mental (Luckow & Cordeiro, 2017).…”
Section: Núcleos Teórico/conceitual E Formação/ Atuação Profissionalunclassified